Esttrutura cromossômica e caracterização cariotípica no gênero Characidium (Teleostei, Characiformes, Crenuchidae) - Scacchetti, Priscilla Cardim [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the present study, eighteen species from the genus Characidium collected at different river basins were analyzed, including C. cf. zebra, C. tenue, C. xavante, C. stigmosum, Characidium sp1, Characidium sp2, Characidium sp3, Characidium sp4, Characidium sp5, Characidium sp6, C. pterostictum, C. vestigipinne, C. rachovii, C. orientale, C. serrano, C. timbuiense, C. vidali e Characidium sp. aff. C. vidali. The analyses involved classical (Giemsa conventional staining and C-banding) and molecular cytogenetic techniques (fluorescent in situ hybridization with ribosomal 5S and 18S, telomeric, microsatellite motifs and U2 snDNA probes, whole chromosome painting using W-specific probe obtained from C. gomesi-CgW). Besides that, DNA sequencing of restriction-associated DNA (RAD) was carried out in males and females of C. gomesi. All species showed diploid chromosome numbers of 2n=50, with karyotypes mainly composed of meta- and submetacentric types, besides the occurrence of supernumerary chromosomes in Characidium sp. aff. C. vidali and one acrocentric pair in C. pterostictum, C. serrano e C. timbuiense. Also, almost all the analyzed species showed a ZZ/ZW sex chromosome system in distinct evolutionary stages, except Characidium cf. zebra, C. tenue, C. xavante e C. stigmosum. The constitutive heterochromatin was located differentially on the W chromosomes and in interstitial and telomeric position on the Z chromosomes, as well as in the B chromosomes of Characidium sp. aff. C. vidali. 5S rDNA was differentially distributed in the different species, with variations on the number of clusters per genome and position in the karyotype, while the 18S rDNA was conserved in number of sites per genome and variable in location. Conversely, the U2 snDNA distribution was conserved in a single homologous chromosome pair in all species, except in Characidium sp. aff. C. vidali and Characidium sp2. Telomeric probes revealed species with several interstitial...

No presente estudo, foram analisadas dezoito espécies de peixes do gênero Characidium, C. cf. zebra, C. tenue, C. xavante, C. stigmosum, Characidium sp1, Characidium sp2, Characidium sp3, Characidium sp4, Characidium sp5, Characidium sp6, C. pterostictum, C. vestigipinne, C. rachovii, C. orientale, C. serrano, C. timbuiense, C. vidali e Characidium sp. aff. C. vidali de diferentes bacias hidrográficas brasileiras, com o uso de técnicas citogenéticas básicas (coloração com Giemsa e bandamento C) e moleculares (hibridação in situ fluorescente com sondas de DNAr 18S e 5S, DNA telomérico (TTAGGG)n e 4 sequências de microssatélites ((CA)15, (GA)15, (CG)15 e (TTA)10), e pintura cromossômica através da microdissecção e amplificação do cromossomo sexual W de C. gomesi (sonda chamada de CgW). Além disso, foi realizado o sequenciamento de DNA associado a sítios de restrição pela enzima SbfI (RAD-tags) através do sistema Illumina Genome Analyzer em machos e fêmeas de C. gomesi. Todas as espécies apresentaram número diploide de 2n=50 cromossomos, com predominância dos cromossomos dos tipos meta e submetacêntricos, além da ocorrência de cromossomos supranumerários em Characidium sp. aff. C. vidali e um par cromossômico acrocêntrico exclusivo detectado em C. pterostictum, C. serrano e C. timbuiense. Foi observada também a ocorrência de um sistema ZZ/ZW de cromossomos sexuais em distintos estágios de diferenciação em todas as espécies, com exceção de Characidium cf. zebra, C. tenue, C. xavante e C. stigmosum. A análise da heterocromatina constitutiva por bandamento C revelou a presença de heterocromatina nos cromossomos sexuais, principalmente no cromossomo W e em blocos intersticiais e/ou teloméricos nos braços longos do cromossomo Z e nos cromossomos Bs de Characidium sp. aff. C. vidali. Sequências de DNAr 5S foram localizadas em diferentes cromossomos, com variação na quantidade de sítios entre as espécies,...
Keywords: Peixe - Pesquisa; Peixe - Genética; Citogenetica; Análise de DNA; Cromossomos sexuais; Sex chromosomes; Fishes